High-flow nasal cannula and non-invasive mechanical ventilation in pediatric asthma exacerbation: two-year prospective observational study in intensive care - Carolina S. Delgado; Alberto García-Salido; María Á. García-Teresa; Amelia Martínez de Azagra-Garde; Inés Leoz-Gordillo; Gema de Lama Caro-Patón; Montserrat Nieto-Moro (Permanyer, 2023)
Background: Asthma is a common cause of admission to the pediatric intensive care unit (PICU). We described and analyzed the therapies applied to children admitted to a tertiary PICU because of asthma. Later, we evaluated high-flow nasal cannula (HFNC) use in these patients and compared their evolution and complications with those who received non-invasive ventilation. Methods: We conducted a prospective observational study (October 2017-October 2019). Collected data: epidemiological, clinical, respiratory support therapy needed, complementary tests, and PICU and hospital stay. Patients were divided into three groups: (1) only HFNC; (2) HFNC and non-invasive mechanical ventilation (NIMV); and (3) only NIMV. Results: Seventy-six patients were included (39 female). The median age was 2 years and 1 month. The median pulmonary score was 5. The median PICU stay was 3 days, and the hospital stay was 6 days. Children with HNFC only (56/76) had fewer PICU days (p = 0.025) and did not require NIMV (6/76). Children with HFNC had a higher oxygen saturation/fraction of inspired oxygen ratio ratio (p = 0.025) and lower PCO2 (p = 0.032). In the group receiving both therapies (14/76), NIMV was used first in all cases. No epidemiologic or clinical differences were found among groups. Conclusion: HFNC was a safe approach that did not increase the number of PICU or hospital days. On admission, normal initial blood gases and the absence of high oxygen requirements were useful in selecting responders to HFNC. Further randomized and multicenter clinical trials are needed to verify these data.